Skeletal growth rates of the cold-water coral Dendrophyllia cornigera for each time interval of a long-term multi-stressor experiment - Cristina Gutiérrez-Zárate; Andrea Gori; Alfredo Veiga; Marta Álvarez; César González-Pola; Maria Rakka; Juancho Movilla; Kristina K Beck; Eva M S Atienza; Rubén Acerbi; Covadonga Orejas (PANGAEA, 2025)
A 9-month aquarium experiment with the cold-water Dendrophyllia cornigera was conducted to investigate the single and combined effects of warming, acidification and deoxygenation on its ecophysiological response. The experiment took place at the Aquarium finisterrae (A Coruña, Spain) between 2022-05-06 and 2023-02-24. Treatment values for each parameter (current in situ vs. global change) were: 12 °C and 15 °C (temperature); ~7.99 and 7.69 (pH); ~8.63 mg/L and 6.45 mg/L (dissolved oxygen concentration). A total of eight treatments (with 3 replicates each, 5 L aquaria) were set up. Inside each aquarium, 3 nubbins of D. cornigera were placed. Skeletal growth for each nubbin was assessed using the buoyant weight technique (Jokiel et al. 1978, Davies, 1989) with an analytical balance (OHAUS AX124, precision 0.1 mg). Dry mass of each nubbin was determined based on the net weight in water, water density and the skeletal density of D. cornigera (2.63 g/cm3, Movilla et al. 2014). Corals were weighted at the end of acclimation and after 2, 4, 6 and 9 months (56, 11, 181 and 267 days, respectively) under the experimental conditions. Skeletal growth rates were calculated for each time interval separately, following the formula described in Orejas et al. (2011) and expressed as %/day.